DISCOURSE IMPLEMENTATION ON SONG LYRIC #2019GANTIPRESIDEN THROUGH ONLINE MEDIA MASS REPORTS - Firdaus, Saiyidinal (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
On June 18, 2018, the public was shocked by a song entitled #2019GantiPresiden, composed by Sang Alang. The music was created as a form of socio-political criticism related to the democratic party in Indonesia in 2019, to be precise, the moment of the presidential election on April 18, 2019. The song #2019GantiPresiden contains an exciting meaning and represents the socio-political reality that occurs in society at the time. Sang Alang's attention indicates that there is a discourse that he wants to build through the song. The author uses Van Dijk's (1997) critical discourse analysis method in reviewing the speech made by Sang Alang through the song lyric #2019GantiPresiden based on the element of text, social cognition, and social context. The song lyric implements the socio-political criticism before 2019 presidential election through online mass media reports. In this study, the song lyric #2019GantiPresiden will be based on the song's stanza, in which each stanza will implement the discourse built through online mass media reports. Based on this phenomenon, the speech developed by the creator and singer of the song #2019GantiPresiden will focus on online mass media reports, which containing the problems regarding the increasing unemployment rate due to the influx of foreign workers, rising basic needs, and the lack of seriousness in eradicating corruption cases. Each stanza of the song contains socio-political criticism of the government's policies because the existing guidelines are not in line with what the people expected. The song #2019GantiPresiden is a manifestation of the aspirations of the people's voices who want change, where the difference is a change in government leadership.